Cultural and creative industries in modern languages. (May 2019) - Ma, Haili
This paper explores Cultural and Creative Industry (CCI) teaching and curriculum development across disciplines, based on a case study of a newly established Cultural and Creative Industry (CCI) programme at the School of Modern Languages, Cardiff University, UK. It illustrates how different academic values and goals influence styles of teaching and curriculum development, and it considers how this drives disciplinary evolution. As CCI increasingly attracts international students, in particular from China's middle-class market, this paper questions the direct 'import' of western CCI for Chinese students, in terms of both content relevance and programme development sustainability. This paper suggests that curriculum evolution should be viewed as key for UK higher education to retain market competitiveness, especially a pending 'Brexit'.